Model Pembelajaran Peer-Correction dalam Meningkatkan Kemampuan Menulis Teks Ekplanasi Siswa Kelas XI SMK Taruna Maritim Nusantara - Marbun, Anugerah Septian Gabriel; Naelofaria, Salmah (Indo-MathEdu Intellectuals Journal, 2025)
The purpose of this study was to analyze and understand how much students' ability is in understanding Indonesian language learning materials through the creation and compilation of explanatory texts, both before and after implementing the peer-correction learning model. The research method used is comparative descriptive analysis, where comparative descriptive analysis. The population in this study were 112 students of class XI of SMK Taruna Maritim Nusantara with a sample size of 30 students tested before and after the peer-correction learning method and model were developed. Data collection techniques were carried out through observation studies, questionnaire distribution, and documentation studies, where the data analysis used comparative data analysis. According to the research results, it can be concluded that before the implementation of the peer-correction learning model and method, the average grade XI students of SMK Taruan Maritim Nusantara had sufficient scores and the average was in the range of 70-79, whereas after the implementation of the peer-correction learning model and method, the average grade XI students of SMK Taruna Maritim Nusantara had very good scores and the average was in the range of 80-100.